Reviewing two types of addiction - pathological gambling and substance use - Jazaeri, S.A.; Habil, M.H. (2012)
Gambling, including pathological gambling and problem gambling, has received increased attention from clinicians and researchers over the past three decades since gambling opportunities have expanded around the world. Gambling disorders affect 0.2-5.3% of adults worldwide, although measurement and prevalence varies according to the screening instruments and methods used, and availability and accessibility of gambling opportunities. Several distinct treatment approaches have been favorably evaluated, such as cognitive behavioral and brief treatment models and pharmacological interventions. Although promising, family therapy and support from Gamblers Anonymous are less well empirically supported. Gambling disorders are highly comorbid with other mental health and substance use disorders, and a further understanding is needed of both the causes and treatment implications of this disorder. This article reviews definition, causes and associated features with substance abuse, screening and diagnosis, and treatment approaches.